LA FÁBULA GRECOLATINA EN LOS ADAGIA DE ERASMO Y SU INFLUENCIA EN EL HUMANISTA FERNANDO DE ARCE - Serrano Cueto, Antonio (Myrtia, 1992)
The paper deals with the importance of Erasmus’ ’Adagia’ a a mediator work between the classical literature and the literature of Renaissance, taking as a reference point the fable. To illustrate it, two Latin fables of the humanist Ferdinandus Arcaeus are analysed.